Effect of cold storage and different ions on the thermal resistance of B. cereus NZAS01 spores- analysis of differential gene expression and ion exchange. (February 2019) - Soni, Aswathi; Oey, Indrawati; Silcock, Patrick; Permina, Elizabeth; Bremer, Phil J.
Abstract: Bacillus cereus spores in food are able to survive pasteurization, and if conditions are favourable, subsequently germinate, grow and produce toxins causing food poisoning. The objectives of this study were to firstly determine the impact of cold storage and ion uptake on the thermal resistance of B. cereus spores and secondly to use differential gene expression to help elucidate possible molecular mechanisms for the changes detected in their thermal resistance. B. cereus spores were held at 4 °C in either 0.05 or 0.5 M solutions of cations (Na +, Ca 2+ Mg 2+, K +, Zn 2+ ) for 6 days and their D88 -values were estimated. In the presence of sodium chloride (0.05 and 0.5 M), sodium phosphate buffer, (pH 7, 0.05 and 0.5 M) or zinc acetate (0.05 M), D88 values decreased by 8.8, 10.9, 11.2, 12.9, and 10.2 min respectively, with no evidence of germination (plating methods). Exposure of spores to Na + in sodium phosphate buffer (pH 7, 0.05 and 0.5 M) or sodium chloride (0.05 and 0.5 M) resulted in the accumulation of Na + (66.0 ± 2.9, 193.1 ± 4.6, 136.2 ± 9.9 and 70.5 ± 2.7 μg/g) by spores at the significant expense of K + (10.8 ± 0.5, 7.5 ± 0.2, 8.1 ± 0.4 and 3.6 ± 0.4 μg/g respectively). The mechanism behind the loss of resistance in sodium phosphate buffer (0.05 M) was further investigated by monitoring the differential gene expression using mRNA sequencing. Genes encoding for uracil permease (BC_3890), Mg 2+ P-type ATPase-like protein (BC_1581), ABC transporter ATP-binding protein (BC_0815), and 2-keto-3-deoxygluconate permease (BC_4841) were significantly (FDR value ≤0.05) upregulated. This upregulation indicated a possible increase in permeability, which is suggested to account for the increased uptake of sodium ions and the reduction measured in the spore's thermal resistance. This data suggests that during storage at 4 °C in the presence of sodium ions, spores should not be considered to be completely dormant. Graphical abstract: Unlabelled Image Highlights: Cold storage increases the permeability of Bacillus cereus spores. Uptake of sodium ions reduces the thermal resistance in B. cereus spores. Genes of peptide and ion transport are upregulated in cold storage. Cold storage is a potential hurdle step before inactivation of B. cereus spores.